HUBUNGAN ANTARA PENDIDIKAN DAN PELATIHAN DENGAN PENERAPAN ASUHAN PERSALINAN NORMAL DI RUMAH SAKIT MUHAMMADIYAH PALEMBANG - Endah Sulistyorini; Iin Parlena (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2012)
Education Normal Reproduction aims to promote the survival and achieve a high level of health for mother and baby through the various efforts that are integrated and complete and minimal intervention so that the principles of safety and quality of service can be maintained at optimum levels. This study aims to determine the relationship of education and training of midwives by the application of APN in RS Muhammadiyah Palembang in 2010, is expected to know the relationship between these variables can be used as input for other midwives in providing health services, especially in childbirth aid. This research is a quantitative method with cross sectional approach. The population in this study are all midwives working in midwifery space Muhammadiyah Hospital, Kilkenny, with a sample of 16 respondents who were taken with a total sampling techniques. Data analyzed through univariate and bivariate analysis. Based on the results of bivariate analysis using chi-square statistical test showed in The midwife education variable can not be analyzed because of all the respondents who numbered 16 people all educated DIII midwifery. Midwife training at variable X 2 count (0.034) <X 2 table (3.481) with α = 0.05, there is a relationship between training midwives to the implementation of a normal delivery care. We can conclude that there is a relationship of education and training of midwives with the application of normal delivery care. Recommended that midwives can further improve health services, especially in childbirth aid by applying the normal delivery care.